BARRIERS TO SEEK DEADDICTION SERVICES IN SUBJECTS WITH ALCOHOL USE DISORDER – A CROSS SECTIONAL STUDY - PB Sajeev Kumar; Niranjan Prasad; Amal Abraham; Vinayak Madangopal; Zoheb Raj; Akash Balu and OK Narayanankutty (Kerala Journal of Psychiatry, 2015)
Background: Kerala consumes 8.3 liters of liquor per person annually, the highest in India. Various factors have been identified as barriers among subjects with Alcohol Use Disorder (AUD) in approaching psychiatric care centers for deaddiction treatment. Aims & Objectives: (1) To identify barriers to seek alcohol deaddiction treatment in subjects with AUD. (2) To assess their perception about the new alcohol regulation policy of the Government of Kerala. Methodology: A purposive sample of 100 people with AUD at two government run alcohol outlets of Kannur district were interviewed with a self-rated questionnaire (Barriers Questionnaire v.1.0A–CASAA Research Division) over a period of one month. Their sociodemographic variables were also collected. Results: The main treatment barriers were lack of need (79%), confidence of handling problem on their own (77%), risk of losing job and friends (70%), privacy concerns (71%), lack of time (53%), embarrassment to patient and family (51%), financial burden (59%) and fear of treatment (59%). Majority (68%) supported new regulations by the government, but pointed out the need to create awareness among public regarding ill effects of substance use and to check the rise in usage of illicit drugs. Conclusion: Several barriers prevent people in Kerala from seeking deaddiction for AUD. These need to be considered during making of policies and implementation of treatment strategies.